1996
DOI: 10.1074/jbc.271.13.7330
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Functional Effects of Transcriptional Factor Sp1 on the Murine Interleukin-6 Promotor

Abstract: The NF-kappaB and NF-IL6 elements have previously been shown to play an important role in regulation of both the mouse and human interleukin-6 gene. Between these two elements lies a G/C-rich sequence, which contains three repeats of the element CCACC, protein binding to which has not been previously characterized. In this study we demonstrate that the transcription factor Sp1 binds to these repeats and plays an important role in basal and in inducible expression of the murine interleukin-6 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
4
32
0
Order By: Relevance
“…Sp1 is a ubiquitously expressed transcription factor that binds to GC/GT-rich elements and regulates a variety of genes in a constitutive or inducible manner (43,44). One such motif, the CCACC box, has been shown to be essential for Sp1 binding and promoter function in several genes by invariably activating transcription (35,45,46). Sp1 is a multifunctional protein that can directly interact with the basal transcription complex, as recently shown for the MMP-2 proximal promoter (47), or alternatively function as a more general transcription factor and play an important role in directing tissue-specific expression (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 is a ubiquitously expressed transcription factor that binds to GC/GT-rich elements and regulates a variety of genes in a constitutive or inducible manner (43,44). One such motif, the CCACC box, has been shown to be essential for Sp1 binding and promoter function in several genes by invariably activating transcription (35,45,46). Sp1 is a multifunctional protein that can directly interact with the basal transcription complex, as recently shown for the MMP-2 proximal promoter (47), or alternatively function as a more general transcription factor and play an important role in directing tissue-specific expression (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…While we have not conclusively demonstrated that Areg, Ereg, Btc, or Il6 gene expression is regulated by NF-kB p65 or p52, several studies have demonstrated that Il6 gene expression is positively regulated by p65 (Kang et al 1996, Chen et al 2008, Ndlovu et al 2009). Conversely, our data suggest that decreased phosphorylation of p65 and/or increased processing of p52 may directly or indirectly contribute to the synergistic effects of cAMP and IGF1 on Il6 mRNA abundance.…”
Section: Discussionmentioning
confidence: 55%
“…2B), which is also produced by macrophages on activation [38]. It has been previously shown that BALB/c3T3 can produce a high amount of IL-6 after LPS (1 µg/mL) treatment [39]. Thus, Fig.…”
Section: Discussionmentioning
confidence: 78%
“…First, in the experiments reported here, LPS and IFN-␥ have been washed away before target cells were added to the culture, resulting in little being present to activate IL-6 production by 3T3-VSV. Second, the level of LPS used to activate the macrophages was 100 times less than that used by Kang et al [39] even before the macrophages were washed. Third, the levels of IL-6 in our negative control groups, including unactivated macrophages with either target cell, were always below detectable limits (1.25 units/mL).…”
Section: Discussionmentioning
confidence: 94%